Ionic Liquids in Pharmaceutics: Biocompatibility, Physicochemical Properties, and Applications of API-ILs in Modern Drug Delivery Systems - Abdulnabi, Shams A.; Allami , Mohammed S. (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Ionic liquids (ILs) have emerged as highly versatile solvent systems distinguished by tunable physicochemical properties, negligible vapor pressure, and broad solvation capacity, positioning them as promising alternatives to conventional organic solvents in pharmaceutical science. Specific Background: Increasing proportions of drug candidates exhibit poor aqueous solubility, polymorphic instability, and limited bioavailability, challenges that hinder formulation efficiency and therapeutic performance. Knowledge Gap: Although ILs have been widely explored as green solvents and catalysts, their potential as active pharmaceutical ingredient–ionic liquids (API-ILs) remains insufficiently characterized, particularly regarding biocompatibility, pharmacokinetics, and translational feasibility. Aims: This review synthesizes current advances in IL design, physicochemical behavior, and biomedical applications, with a focus on API-ILs as emerging platforms for drug delivery and solubility enhancement. Results: Evidence shows that ILs can significantly improve solubility, permeability, stability, and crystalline behavior of diverse APIs, while certain API-ILs exhibit dual pharmacological activity and enhanced antimicrobial or transdermal performance. Novelty: The work consolidates the evolution of IL generations, mechanochemical synthesis strategies, and structure–activity relationships governing their pharmaceutical utility. Implications: API-ILs represent a transformative approach for overcoming long-standing formulation barriers, underscoring the need for expanded in vivo studies to validate their safety, biocompatibility, and therapeutic potential in modern drug-delivery systems.Highlight : API-ILs address solubility, bioavailability, and polymorphism issues in poorly water-soluble drugs. Ionic liquids offer tunable physicochemical properties that support improved drug delivery and stability. Biocompatible ILs provide greener alternatives for synthesis while enhancing permeability and therapeutic performance. Keywords : Ionic liquids (ILs), API-ILs, Dissolution, Poorly Water-Soluble Drugs, Drug Development